Odpowiedzi

2010-01-25T19:15:14+01:00
1. -8z + 5 = -z - 1
6=7z|:7
6/7=z
2. -2m + 7 = m - 6
13=3m|:3
13/3=m
3. 6 - 5x = 2x - 7
13=7x|:7
13/7=x
4. -5t + 1 = 8 - 6t
t=7
Najlepsza Odpowiedź!
  • HBK
  • Początkujący
2010-01-25T19:16:04+01:00
1. -8z + 5 = -z - 1
-8z+z=-1- 4
-7z = -5

2. -2m + 7 = m - 6
-2m + m = -6+7
-m = 1 /:(-1)
m=-1

3. 6 - 5x = 2x - 7
-5x-2x = -7-6
-7x = -13 /:(-7)
x=

4. -5t + 1 = 8 - 6t
-5t+6t = 8-1
t = 7
2010-01-25T19:19:16+01:00
1. -8z + 5 = -z - 1
-6=-7z
z=-6/7

2. -2m + 7 = m - 6
-3m=-13
m=- 13/3

3. 6 - 5x = 2x - 7
-13=-7x
x=-13/7

4. -5t + 1 = 8 - 6t
t=7